2015
DOI: 10.1507/endocrj.ej14-0510
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of islet autotransplantation after total pancreatectomy in chronic pancreatitis patients [Review]

Abstract: Abstract. Islet autotransplantation (IAT) is a viable treatment for patients with severe chronic pancreatitis, this modality may prevent brittle diabetes mellitus after pancreatectomy. This systematic review and meta-analysis was performed to evaluated the outcomes of IAT after TP and discuss the factors that may affect the efficacy of this procedure. MEDLINE, Embase, Web of Science and the Cochrane Central Register of Controlled Trials (CENTRAL) were searched from 1977 to 30 April 2014. Cohort Studies reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Two systematic reviews which carried out metaanalyses reported pooled insulin independence rates of 27% (95% CI: 21-33%) and 28.4% (95% CI: 15.7-46.0) at one year and 21% (95% CI: 16-27%) and 19.7% (95% CI: 5.1-52.6%) at two years, respectively [44,45].…”
Section: Group 4-atypical Presentation Of Cpmentioning
confidence: 99%
“…Two systematic reviews which carried out metaanalyses reported pooled insulin independence rates of 27% (95% CI: 21-33%) and 28.4% (95% CI: 15.7-46.0) at one year and 21% (95% CI: 16-27%) and 19.7% (95% CI: 5.1-52.6%) at two years, respectively [44,45].…”
Section: Group 4-atypical Presentation Of Cpmentioning
confidence: 99%
“…At the same time TP is proposed, with or without simultaneous auto-islet transplantation, for some types of chronic pancreatitis [7] and also for the treatment of locally advanced pancreatic cancer requiring arterial resection and reconstruction [8]. Total pancreatectomy combined with autologous islet transplantation has also been proposed for patients with a high-risk for complications resulting from the pancreatic anastomosis [9].…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al reported rates at 1 and 2 years follow-up off 28.4% and 19.7%, respectively. 37,38 Also a clinical dilemma is the treatment of patients with CP and an enlarged pancreatic head. About half of the responder would opt for a PPPD, while the other half would perform an endoscopic treatment first.…”
Section: Discussionmentioning
confidence: 99%